2016
DOI: 10.1007/s10854-016-5031-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of nanostructured lithium titanate by simple peroxo route

Abstract: Li 4 Ti 5 O 12 nanopowder was successfully synthesized by simple peroxo-solution growth technique. The physicochemical properties of synthesized powders were studied by powder X-ray diffraction spectroscopy, Fourier transform infrared spectroscopy, Raman spectroscopy and Scanning electron microscopy. The effect of calcination on structure, morphology and the electrochemical performances of Li 4 Ti 5 O 12 have also been investigated. The electrochemical property of the Li 4 Ti 5 O 12 was analyzed by galvanostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…The crystallization of anatase found by DSC was slightly higher compared to the results achieved by HT-XRD (differences can be caused by different temperature programs and atmosphere), but the order of crystallization was the same. Similar exothermal transformation to anatase at approximately 425 °C was recorded in lithium titanates in the works by Selvamurugan et al 21 and Motlochováet al 27 Over 700 °C, a broad exothermic peak emerged on DSC curves connected with gradual crystallization to rutile, in agreement with Ryu et al 28 The transformation temperatures to rutile or titanates according to DCS are shown in Table 3. Transformation temperatures of sodium and potassium The FTIR spectra of all samples contained O−H stretching vibration of water (surface-adsorbed or coordinated to TiO 2 ) at ∼3440 cm −1 .…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The crystallization of anatase found by DSC was slightly higher compared to the results achieved by HT-XRD (differences can be caused by different temperature programs and atmosphere), but the order of crystallization was the same. Similar exothermal transformation to anatase at approximately 425 °C was recorded in lithium titanates in the works by Selvamurugan et al 21 and Motlochováet al 27 Over 700 °C, a broad exothermic peak emerged on DSC curves connected with gradual crystallization to rutile, in agreement with Ryu et al 28 The transformation temperatures to rutile or titanates according to DCS are shown in Table 3. Transformation temperatures of sodium and potassium The FTIR spectra of all samples contained O−H stretching vibration of water (surface-adsorbed or coordinated to TiO 2 ) at ∼3440 cm −1 .…”
Section: Resultssupporting
confidence: 85%
“…The crystallization of anatase found by DSC was slightly higher compared to the results achieved by HT-XRD (differences can be caused by different temperature programs and atmosphere), but the order of crystallization was the same. Similar exothermal transformation to anatase at approximately 425 °C was recorded in lithium titanates in the works by Selvamurugan et al and Motlochová et al…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations